Predicting of The Transportation Solid Waste Cost in the Alang-alang Lebar Sub-District, Palembang City - Ramadhani, Ramadhani; Aminuddin, Kiagus Muhammad; Bethary, Rindu Twidi (Jurnal Fondasi, 2024)
An MSW management system's transportation subsystem is responsible for collecting and transporting waste. For the MSW management system, the cost of solid waste transportation is a crucial factor. As a result, research will be done on the study of solid waste transporting costs. The objective of this paper is to look into the transportation costs, daily travel time, and routes in the Alang-alang Lebar neighborhood. The methodologies used in this study make reference to SNIs 19-3964-1994, 19-2454-2002, and 03-3243-2008 in order to calculate the waste volume and transport time. The total transport time by dump trucks in the Alang-alang Lebar sub-district ranges from 5.45 - 10.27 hours/day with total cost of transportation per day ranging from IDR 3,618.0 - IDR 3,751.7/km. The total cost of transporting solid waste by dump trucks in Alang-alang Lebar District per day is IDR 576,904.8 or IDR 49,372.1/m3